Keamanan Kognitif dan Disinformasi dalam Perang Rusia–Ukraina 2022: Analisis Strategi dan Implikasi Keamanan Nasional - Nur Rafa Tsabitah Ruslan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
As evidenced by the way the Russia–Ukraine War has been fought since 2022, the military battlefield is no longer confined to physical borders but also extends into the realm of the human mind through disinformation and psychological operations. This paper examines the production and dissemination of disinformation by state and non-state actors to shape public perceptions, divide domestic opinion, and delegitimize opponents on the international stage. In this context, disinformation in the post-truth era is portrayed as “a 21st-century asymmetric warfare tool that utilizes social media and digital technologies to amplify constructed narratives.” In a world that depends on the global information space, cognitive vulnerabilities and the ability to verify facts have become critical factors in maintaining national security, political stability, and social cohesion. This paper presents an analytical framework for assessing cognitive security approaches and advocates education at all levels to strengthen information resilience through the design of digital literacy training programs. It also proposes integrating strategic communication functions into the national defense architecture.